MINAT BELAJAR MAHASISWA PADA MATA KULIAH MEDIA PEMBELAJARAN MELALUI PENERAPAN PEMBELAJARAN BERBASIS PROYEK - Indah Suciati; Hajerina; Dewi Sri Wahyuni (JURNAL PENDIDIKAN, 2022)
The a low interest in student learning in learning media courses, so it is necessary to apply project-based learning. To describe student interest in learning media courses through project-based learning, descriptive research is used. The learning interest scale is given to mathematics education students for the 2022–2023 academic year of Alkhairaat University. Furthermore, 4 students who have an interest in learning in the high and medium categories were selected as research subjects through purposive sampling. Data were collected through questionnaires and structured interviews. Data analysis refers to the Miles & Huberman model and data triangulation techniques to see the validity. The findings describe five indicators of student interest in learning in the high and medium categories. The findings also provide an overview, namely (1) project-based learning can develop and increase student interest in learning media courses, (2) problem-solving skills, creative thinking, and communication skills related to student interest in learning can be improved through project-based learning.